Evaluasi Keberhasilan Gerakan Indonesia Sadar Pajak Tahun 2018 - Septian Bayu Kristanto; Vira Anggaraeni (InFestasi, 2019)
Tax revenues accounted for more than 80% and therefore, a high level of public awareness of taxes was needed. So the Directorate General of Taxes made various efforts to increase public awareness of taxes and one of them was the Tax Awareness Indonesia Movement program. The research entitled "Evaluation of the Success of the Tax-Conscious Indonesian Movement in 2018", aims to determine the level of success, goals that have been achieved and the factors that influence the lack of public awareness of taxes during 2018. With qualitative data, primary and secondary data sources, data obtained through direct interviews and also from various other sources. With descriptive data analysis methods and also triangulation data collection techniques consisting of participatory observation, in-depth interviews and documentation. Based on the data analysis carried out, it was concluded that the Indonesia Tax Awareness Movement of 2018 was successful, because it had a success rate above 50%. Whereas for the purpose during 2018 it has not been reached optimally, because there are 47% of respondents who stated that both of these goals have not been achieved. For the causes of the lack of public awareness of very large taxes is influenced by factors that lack understanding of taxes.